2016
DOI: 10.1038/nature18296
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian Zika virus strain causes birth defects in experimental models

Abstract: Summary Zika virus (ZIKV) is an arbovirus belonging to the genus Flavivirus (Family Flaviviridae) and was first described in 1947 in Uganda following blood analyses of sentinel Rhesus monkeys1. Until the 20th century, the African and Asian lineages of the virus did not cause meaningful infections in humans. However, in 2007, vectored by Aedes aegypti mosquitoes, ZIKV caused the first noteworthy epidemic on the island of Yap in Micronesia2. Patients experienced fever, skin rash, arthralgia and conjunctivitis2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,134
6
49

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,171 publications
(1,299 citation statements)
references
References 36 publications
68
1,134
6
49
Order By: Relevance
“…Recently, a few studies [79,80,[82][83][84][85] have evidenced the pathogenic potential of Brazilian strain of ZIKV during the development of fetus in animal models. These studies concluded that ZIKV first infects the placenta and then the brain of fetus, where it preferentially infects neural progenitor cells and decreases their viability and growth as neurospheres through down-regulation of genes that are involved in cell and organ development, and up-regulation of genes that are involved in immune responses.…”
Section: Pathogenesis Of Microcephalymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a few studies [79,80,[82][83][84][85] have evidenced the pathogenic potential of Brazilian strain of ZIKV during the development of fetus in animal models. These studies concluded that ZIKV first infects the placenta and then the brain of fetus, where it preferentially infects neural progenitor cells and decreases their viability and growth as neurospheres through down-regulation of genes that are involved in cell and organ development, and up-regulation of genes that are involved in immune responses.…”
Section: Pathogenesis Of Microcephalymentioning
confidence: 99%
“…This results in inhibited cellular proliferation and differentiation, neuronal apoptosis, thinning of the cortex and macroscopic features similar to microcephaly. Based on the results of the above stated studies [79,80,[82][83][84][85], a causal link between ZIKV infection and microcephaly could be hypothesized.…”
Section: Pathogenesis Of Microcephalymentioning
confidence: 99%
“…Several research groups applied the brain organoid model to study Zika infection, a current epidemic that has been strongly linked to newborn microcephaly 35, 46, 47, 48, 49, 50. These studies have provided evidence that human neural stem cells are selectively vulnerable35, 48 and more susceptible to premature differentiation50 upon Zika virus infection, providing a molecular explanation for the observed microcephaly.…”
Section: Translational Applications Of Brain Organoidsmentioning
confidence: 99%
“…Thus, 2D neuronal cultures could possibly recapitulate only cellular defects occurring during early stages of brain development and the findings obtained from such models must be cautiously interpreted. Recently, the development of 3D culture system resulting in brain organoids has been reported, [36][37][38] offering more closely relevant in vitro models for mature brain organization and cellular network. Different differentiation protocols have been developed and fine-tuned to generate organoids with different particular brain region identity, 37,39 potentially allowing study of pathological effects focusing on specific yet complex 3D brain-like structures.…”
Section: Gtf2ird1mentioning
confidence: 99%